SERANGAN PENGGEREK BATANG KAKAO DI KOTA PAYAKUMBUH, SUMATERA BARAT - Yudha, Pajri; Indra Dwipa (Universitas Veteran Bangun Nusantara, 2024)
Cocoa stem borer (CSB) (Zeuzera coffeae) is a main pest on cocoa plant. The research aimed to study the CSB attack in cocoa plantation in Payakumbuh. The research was conducted in cocoa plantation of Payakumbuh from November 2023 to February 2024. Survey method was used in the study and purposive random sampling was used to determine sampling. The criteria to determine locations were ± 0.5 hectare of cocoa plantation and cocoa age was ± 4 years. According to criteria, 2 districts were chosen, Lamposi Tigo Nagari and Payakumbuh Timur. In each district, 5 sub-districts were chosen and in each sub-district, 2 cocoa plantations were chosen. The imaginary diagonal line was formed to determine sampling plants. The result showed that the percentage of attacked plant by Z. coffeae was 0.75% and percentage of attacked stem and branch was 0.70%